Effect of process parameters on microhardness and microstructure of heat affected zone in TIG welded X65-HSLA steel - Musa, Hussin Abdullrhman; Maleque, Md. Abdul; Ali, Mohammad Yeakub (2017)
The objective of the present article was to study the influence of welding parameters (current, arc voltage, travel speed and heat input) on microhardness, depth, and microstructure of the heat-affected zone (HAZ) and to optimize the process parameters after accomplishment of the TIG welding process on X65 steel following suitable Taguchi experimental design. Microstructures of the welded samples were studied to analyze the changes in the microstructure of the material in terms of ferrite, pearlite, bainite, and martensite formations. Welding speed was found to be the most significant factors leading to changes in microhardness and metallurgical properties. The microhardness tended to increase significantly with the increase of welding speed from 1.0 to 2.5 mm/s whereas the width of HAZ decreased. The current and arc voltage were found to be less significant in relative comparison. The increase of welding heat input caused an increase in width (depth) of HAZ and the growth of prior austenite grains and then enlarged the grain size of coarse grain heat affected zone (CGHAZ). However, the amount of martensite in HAZ decreased accompanied by an opposite change of bainite. It can be concluded that the mechanical properties and the microstructural of HAZ area was strongly affected by the welding parameters.